La política bajo sospecha. Regularidades y reformulaciones de la vigilancia política en Argentina: la policía de Santiago del Estero - Paulo Román Margaría; Celeste Schnyder (Nuevo mundo - Mundos Nuevos, 2015)
Despite the change of political regime and the recovery of the rule of law, the political and ideological espionage agencies remained within the argentine police forces. From the case of a policial intelligence agency of a province in argentine northern, we investigate the regularities and reformulations in the police classification logics and intervention modalities employed to manage the political order in different political-institutional moments that crossed the country in the second half of the twentieth century. The analysis of intelligence reports belonging to the Department of Police Information of Santiago del Estero, active since the 50s until 2004, allows us to question the dichotomous perspectives about the argentinian recent past that opposes authoritarianism-democracy, violence-politics and security forces-civil society. The archives of the repression are the material expression of institutionalization, beyond the boundaries between political regimes, of a state logic that found in the political-ideological control an instrument of preservation of the established order.